ABOUT SOME PECULIARITIES OF KOMI-PERMYAK CHRONONYMICS (Philological Studies, 2019)
Description of Komi-Permyak chrononyms – names of holidays, meteorological and sacred events, meaningful economically and socially is given in the article. Different types of semantics chrononyms are singled out (meteorological, botanical, commercial, religious), mythological motivation of periods of time names (reflected in the names of archaic cults of plants, birds, animals, orthodox saints) is examined. Conclusion, concerning the fact that despite the influence of calendar events of the Russian national calendar on Komi-Permyak system, it is different in specific ritual content, is made.
Keywords: symbolism of national calendar, Komi-Permyak calendar ritual terminology, ways of formation and peculiarities of functioning of ritual origin phraseology